Ethics and humanism in medical’s training - Perales Cabrera, Alberto (Acta Bioethica, 2008)
The claim to emphasize the ethic and humanistic axes of the medical education in the XXI" century leans not only on the repeated observation of doctors’ professional misconducts, but also on the System of Health Care’s inequities which often violate the patients’ rights and arise society’s complaints. A serious effort must be done to improve the ethic and humanistic medical training which must be inserted in an adequate theory of man’s moral development, and start from a critical reflection about the requests that underlie that training, theprofessors and the procedures and sceneries that are employed to reach that aim.